Characterisation of polyphenol oxidase from Melissa officinalis L. subsp. officinalis (lemon balm) - Serap DOĞAN; Yasemin AYYILDIZ; Mehmet DOĞAN; Ümran ALAN; Mehmet Emin DİKEN (Czech Journal of Food Sciences, 2013)
Polyphenol oxidase (PPO) from Melissa officinalis L. subsp. officinalis (lemon balm) was partially purified by ammonium sulphate precipitation and dialysis; and then it was characterised in detail in terms of pH and temperature optima, thermal stability, kinetic parameters, and inhibition properties. Based on experimental results, it was found out that (i) the optimum pH and temperature values of PPO were 6.5, 4.0, and 8.5 and 40, 50, and 60°C for catechol, 4-methylcatechol and pyrogallol substrates, respectively; (ii) the best substrate was pyrogallol due to the highest Vmax/Km value, followed by catechol and 4-methylcatechol; (iii) enzyme activity decreased due to heat denaturation of the enzyme with increasing temperature and inactivation time for all substrates; (vi) gallic acid and l-glutamic acid did not inhibit PPO; and (v) the most effective inhibitor was glutathione. Furthermore, the phenolic and protein contents of lemon balm extract were also determined according to the Folin-Ciocalteu and Bradford methods, respectively.